1997
DOI: 10.1037/0022-3514.72.6.1460
|View full text |Cite
|
Sign up to set email alerts
|

Links between race/ethnicity and cultural values as mediated by racial/ethnic identity and moderated by gender.

Abstract: Two studies examined whether individualism (orientation toward one's own welfare), collectivism (orientation toward the welfare of one's larger community), and familism (orientation toward the welfare of one's immediate and extended family) are distinct cultural values predicted by race/ ethnicity. The 3 constructs proved to be separate dimensions, although collectivism and familism were positively correlated. In Study 1, persons of color scored higher on collectivism and familism than did Anglos. No differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
252
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(280 citation statements)
references
References 82 publications
22
252
2
Order By: Relevance
“…On self-description tasks, participants generate more aspects of their individual self than their collective self regardless of levels of collectivism and individualism (Gaertner et al, 1999, Investigation 4;Ybarra & Trafimow, 1998, Experiment 3) and culture of origin (Trafimow et al, 1991). Furthermore, persons of color (i.e., African Americans, Asian Americans, and Latinos) score higher than do Anglos on measures of collectivism, yet they score just as high as Anglos on measures of individualism (Freeberg & Stein, 1996;Gaines et al, 1997).…”
Section: The Universality Of Individual-self Primacy: Culture As a Momentioning
confidence: 99%
“…On self-description tasks, participants generate more aspects of their individual self than their collective self regardless of levels of collectivism and individualism (Gaertner et al, 1999, Investigation 4;Ybarra & Trafimow, 1998, Experiment 3) and culture of origin (Trafimow et al, 1991). Furthermore, persons of color (i.e., African Americans, Asian Americans, and Latinos) score higher than do Anglos on measures of collectivism, yet they score just as high as Anglos on measures of individualism (Freeberg & Stein, 1996;Gaines et al, 1997).…”
Section: The Universality Of Individual-self Primacy: Culture As a Momentioning
confidence: 99%
“…However, given that neither the 1-factor model nor the 2-factor model provided an acceptable fit, the results of this comparison are insufficient to justify accepting either model (unlike Phinney & Ong, 2007). In order to obtain a 1-factor or a 2-factor model with adequate fit to the data, we would have needed to add several unexpected instances of uncorrelated measurement error (as did Avery et al, 2007;Gaines et al, 1997;and Roberts et al, 1999). Although the addition of uncorrelated measurement error terms can be justified in some cases (Kline, 2005), we decided not to employ this technique.…”
Section: Confirmatory Factor Analysis 2-factor Model Allmentioning
confidence: 99%
“…Various researchers in the U.S. (e.g., Avery et al, 2007;Gaines et al, 1997;Ponterotto et al, 2003) similarly have concluded that the MEIM measures overall (i.e., global) ethnic identity.…”
Section: Psychometric Properties Of the Meim: Ethnic Identity As A Unmentioning
confidence: 99%
See 2 more Smart Citations